Australian doctors' knowledge of and compliance with the law relating to end-of-life decisions: implications for LGBTI patients. Issue 8 (3rd August 2018) - Cartwright, Colleen; White, Ben; Willmott, Lindy; Parker, Malcolm; Williams, Gail
Abstract: In most developed countries, competent patients have the legal right to refuse any medical treatment; Advance Care Planning mechanisms extend this right to non-competent patients. However, some groups, including lesbian, gay, bisexual, transgender and intersex (LGBTI) people, risk their wishes not being respected if they lose capacity, more than others. Little is known about medical practitioners' knowledge of, or attitudes to, the law in this area, especially in relation to LGBTI people, or how the law influences their decision-making. An Australian postal survey explored knowledge and attitudes of medical specialists to legal issues relating to withdrawing/ withholding life-sustaining treatment from adults without capacity. One scenario (the focus of this paper) asked which of four plausible substitute decision-makers, including a same-sex partner, had the legal authority to make such decisions. The overall response rate was 32% (867/2702). Less than one-third of respondents correctly identified the same-sex partner as the legally authorised decision-maker. LGBTI people face multiple obstacles to having their end-of-life wishes respected. Where healthcare providers are also ignorant of the partner's legal right to make such decisions, the problem is compounded. Improved legal education for clinicians and promotion of educational resources for members of the LGBTI community is needed.